ANALISIS SISTEM KESIAPSIAGAAN RUMAH SAKIT UMUM DALAM MENGHADAPI BENCANA DI KABUPATEN SLEMAN - , KUDIYANA, Prof. dr. Laksono Trisnantoro, MSc. PhD. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sleman district has high potential to disaster. Hospital has low level on preparedness to anticipate disaster. Hospital should prepare the hospital disaster plan as mandated by the law and also to fulfill the hospital accreditation. Writer would like analyze the hospital preparedness in general hospital in Sleman District. The objective of this research is to determine the level of hospital preparedness in facing disaster and to analyze the factors that inhibit the implementation of hospital disaster plan and to determine the coordination system among the hospital to anticipate disaster. This research using quantitative methods with descriptive statistic approach. The sampling methods using census by taking all the general hospitals in Sleman District as a sample. The variable used in this research are hospital disaster plan documents and disaster simulation. Another variable is the coordination system plan among the hospitals. Data collected using questionnaire and checklist. This research conducted in february-Mei 2014. Data analyzed using descriptive statistic. The result of this research showed that 21% general hospital in Sleman District has a hospital disaster plan. Budget, there is no policy of the hospital leadership is afactor that inhibits the general hospital preparedness. There is no coordination system planning among the hospitals in facing disaster. The hospital preparedness in Sleman District is on low level of preparedness as can be seen that only 21 % hospital has a hospital disaster plan. Key Words : Preparedness, general hospital, disaster